Male identification, generic classification and sexual dimorphism of Micronychus pardus (Kazantsev, 2018) comb. nov. (Coleoptera: Lycidae: Calochrominae) - Motyka, Michal (Zootaxa, 2019)
Almost all net-winged beetles are members of Müllerian complexes and their similarity due to phenotypic coevolution sometimes complicates species identification and generic placement. Therefore, large specimen series, detailed exhaustive examination of morphological characters and molecular data are needed to clarify the taxonomic placement. Using mitochondrial DNA sequences, I investigated the sexual dimorphism and generic placement of the recently described species Calochromus pardus Kazantsev, 2018. I found that the species does not belong in Calochromus Guérin-Méneville, 1833 and all morphological characters and molecular analyses point to its placement in Micronychus Motschulsky, 1861. Therefore, Micronychus pardus (Kazantsev, 2018), comb. nov. is proposed. Additionally, the male is described here for the first time showing the sexual dimorphism in the species. Unlike the females, the males do not superficially resemble members of Xylobanus Waterhouse, 1879 with bright coloured elytral costae and black background, but mimics the sympatrically occurring yellow and black lycids in the genus Cautires Waterhouse, 1879.